PENGARUH PENERAPAN PEMBELAJARAN AKTIF TIPE SYNERGETIC TEACHING TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 1 LENGAYANG KABUPATEN PESISIR SELATAN TAHUN PELAJARAN 2012/2013 - Susanti, Yosi; Rismen, Sefna; K, Delsi (STKIP PGRI Sumbar, 2013)
The research was background by the student comprehension of math concept are still low at SMPN 1 Lengayang. This research is to knowing the student comprehension of math concept that apply active learning type synergetic teaching better than student comprehension of math concept that apply conventional learning in class VIII SMPN 1 Lengayang. The type of research is exsperimen by using Randomized for Subject. The data analysis technique used is t-test one part. The result of hypothesis test with = 3,04 > = 1,64, then the hyphothesis in this research is received. In conclusion, student comprehension of math concept that apply active learning type synergetic teaching better than student comprehension of math concept that apply conventional learning.